TECHNOLOGY TRANSFER OFFICE MODEL - D. Tymchenko (Astana IT University, 2020)
At present creation of specialized organizational structure, the technology transfer office (TTO) in higher education institutions (HEIs) becomes increasingly important for establishing communication between scientists, business, and the state and for implementation of the results of scientific and technical activities of higher education institutions in the real sector of the economy. Surveys of domestic and foreign scientists show that the issues of creating project offices (which in fact are TTOs) in HEIs remain insufficiently explored. Given this, the authors conducted a study of project management to create a TTO in a HEI. Efficient organizational project management requires the presence of Organizational Breakdown Structure. This article proposes an Organizational Breakdown Structure template, which clearly demonstrates the project team structure targeted at TTO creation in a HEI, the subordination and basic functions of each team member. In addition, the article proposes a model of organizational structure of the newly created TTO, which is also a template for HEI, and which defines the structure of the office staff, their subordination and main functions. To determine the location of the TTO in the structure of HEI, the article proposes a corresponding model that shows the subordination and connection of the office with other functional units of HEI. Using the models presented in the article, any HEI will be able to effectively manage the project of creating a TTO and as a result to create a project product – a TTO.